Increasing the Reliability of Test Control Using Information Technologies in Inclusive Physical Education - Blavt, Oksana; Iedynak, Gennadii; Pereverzieva, Svitlana; Holub, Viktor; Melnyk, Svitlana (Physical Education Theory and Methodology, 2023)
The purpose of the study was to determine the reliability and validity of a method developed on the basis of information technologies to control the strength endurance of the core muscles of students with disabilities. Materials and methods. 38 students with disabilities, aged 18–23, who entered the first year of study at the university, voluntarily participated in the study. The studied sample consisted of students with a simple form of disorder in the musculoskeletal system, who have the ability to move independently and perform motor actions. An information-search approach to data collection was used at the theoretical level, and pedagogical testing and methods of mathematical statistics were used at the empirical level. Results. A method for assessing the strength endurance of the core muscles developed on the basis of information technologies is presented. To implement the method, a network of sensors formed by analog and digital sensors, wireless infrared communication devices, information from which enters the programmable logic controller and is fed to the personal computer, is used. The software has been developed that implements immediate processing and presentation of test control results in real-time. Correlation analysis was used to calculate the indicators of test reliability and validity of fixing the results of tests using the method presented in this paper and the traditional method. Conclusions. Experimental verification of the presented method for controlling the development of the core muscles of students with disabilities has proven its practical effectiveness. In conclusion, the numerical values of reliability and validity obtained using the automated method of countering are within the range of “above average,” in contrast to the measurements made by the traditional method of control using a test exercise: the calculation of test reliability and validity revealed a level of “below average.” The set of obtained numerical characteristics of empirical data proved the advantage of using the latest information technologies in inclusive physical education as a factor of its effectiveness. Achieving positive results in ensuring the proper level of health, full physical and psychological rehabilitation of higher education students with disabilities is considered as a practical value of implementing inclusion in a higher education institution.